Ultrasound‐assisted treatment of kaolin artificially contaminated with phenanhtrene, fluoranthene and hexachlorobenzene - Duong, Pham Thuy; Shrestha, Reena Amatya; Sillanpää, Mika; Virkutytė, Jūratė (Journal of Environmental Engineering and Landscape Management, 2010)
Application of ultrasound in decontamination of polluted soil is a new and promising technology. The feasibility of ultrasonic treatment of clayey soil (kaolin) highly contaminated with persistent organic pollutants (POPs), such as phenanthrene (PHE), fluoranthene (FLU), hexachlorobenzene (HCB), was the main target of the work. The laboratory experiments were conducted at various conditions (moisture, power, irradiation duration and the initial concentration of contaminants) and the effects of these parameters on the process efficiency were examined. Experimental results showed that ultrasonication alone has a potential to remove POPs, although the removal efficiencies were relatively low when a short irradiation duration (1–6 hours) was adopted. Intermittent ultrasonication over longer periods (up to the total of 46 hours) increased the removal efficiencies to 45% of HCB and nearly 100% of PHE. The optimum moisture content of the slurry was found to be in the range of 50–70%. The total electric energy consumption during the experiments using the optimum operational conditions (100 W and above ultrasound irradiation power and 67% moisture content) was 1.5 kWh in comparison to 1.84 kWh during experiments utilizing minimum operational conditions.Article in English.Dirbtinai fenantrenu, fluorantenu ir heksachlorobenzenu užteršto kaolino valymas ultragarsuSantrauka. Ultragarsinės radiacijos taikymas dirvai valyti yra nauja, tačiau sparčiai plėtojama technologija. Pagrindinis šio darbo tikslas buvo įvertinti ultragarso poveikį  atsparių organinių teršalų, tokiu kaip: heksachlorobenzenas (HCB), fenantrenas (PHE) ir fluorantenas (FLU), – degradavimui dirbtinai užterštame kaoline. Laboratoriniai eksperimentai atlikti pasirenkant įvairų dirvos drėgnumą, ultragarso intensyvumą, stiprumą, radiacijos trukmę ir pradines organinių teršalų koncentracijas bei įvertinant jų poveikį kaolino valymo efektyvumui. Rezultatai įrodė, kad ultragarsas gali būti taikomas dirvai valyti, tačiau efektyvumas nebuvo itin didelis kaoliną švitinant nuo 1 iki 6 valandų. Taikant kintamą radiaciją (iki 46 valandų), HCB šalinimas pagerėjo iki 45 %, o PHE – net iki 100 %. Valant organinius teršalus optimali kaolino drėgme buvo 50–70 %. Taikant optimalias reakcijos sąlygas (100 W ir daugiau, 67 % drėgmės), elektros energijos sunaudota mažiau (1.5 kWh) nei kai reakcijos sąlygos minimalios (1,84 kWh).Reikšminiai žodžiai: ultragarsas, dirvos valymas, atsparūs organiniai teršalai.Очисткаультразвуком каолина, искусственно загрязненного фенантреном, флуорантеном и гексахлоробензеномРезюме. Применение ультразвуковой радиации для очистки почв является новой, быстро развивающейся технологией. Основной целью работы было оценить воздействие ультразвука на деградацию устойчивых органических загрязняющих веществ, таких, как гексахлоробензен, фенантрен и флуорантен, в искусственно загрязненном каолине. Лабораторные исследования проводились при разной влажности почвы, интенсивности ультразвука, его мощности, длительности радиации и начальных концентрациях органических соединений, а также при учете их воздействия на эффективность очистки каолина. Результаты показали, что ультразвук может применяться для очистки почв, однако эффективность не была высокой при воздействии излучением в течение от одного до шести часов. При применении меняющейся радиации (до 46 часов) эффективность очистки от гексахлоробензена увеличилась до 45 %, а от фенантрена даже до 100 %. Оптимальной для очистки от органических соединений оказалась 50–70 %-ая влажность каолина. Потребление электроэнергии при оптимальных условиях реакции (100 W и больше, 67 %-ая влажность) было меньшим, чем при минимальных условиях реакции (1.84 kWh).Ключевые слова: ультразвук, очистка почв, устойчивые органические соединения.First Publish Online: 10 Feb 2011